Health status of the population in Naqu, Tibet and its latent class analysis: a cross-sectional survey - Cui, Jiaxue; Nima, Ouzhu; Zhaxi, Duoji; Jin, Chenxin; Wang, Ruiqi; Diao, Yizhuo; Chen, Yongxing; Xu, Xiaoguang; Li, Xiaofeng (Frontiers in Public Health, 2023)
Through a survey and analysis of the population's present state of health, it is possible to give data support for improving the health status of inhabitants in Naqu, Tibet. Additionally, it is possible to provide specific recommendations for the development of medical and healthcare facilities in Tibet. The health scores of the participants were based on their responses to the four main sections of the questionnaire: dietary habits, living habits, health knowledge, and clinical disease history, and the variability of health status among groups with different characteristics was analyzed based on the scores. The four major sections were used to create classes of participants using latent class analysis (LCA). Using logistic regression, the factors influencing the classification of latent classes of health status were investigated. A total of 995 residents from 10 counties in Naqu were selected as the study subjects. And their demographic characteristics were described. The mean health score of residents after standardization was 81.59±4.68. With the exception of gender, health scores differed between groups by age, education level, different occupations, marital status, and monthly income. The health status in Naqu, Tibet, was divided into two groups (entropy=0.29, BLRT=0.001, LMRT=0.001) defined as the "good health group" and the "general health group." A monthly income of more than ￥5000 adverse to good health in Naqu, Tibet. Single, well-educated young adults in Naqu, Tibet, have outstanding health. The vast majority of people in Tibet's Naqu region were in good health. Furthermore, the population's latent health status was divided into two classes, each with good dietary and living habits choices, low health knowledge, and a history of several clinical diseases. Univariate and multivariate logistic regression analysis showed that monthly income more than ￥5000 was an independent risk factor for poor health status.